2015
DOI: 10.1177/0301006615594949
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Symmetry of Distortions of Tactile Size Perception

Abstract: The perceived distance between touches on the limbs is generally bigger for distances oriented across the width of the limb than for distances oriented along the length of the limb. The present study aimed to investigate the coherence of such distortions of tactile size perception across different skin surfaces. We investigated distortions of tactile size perception on the dorsal and palmar surfaces of both the left and right hands as well as the forehead. Participants judged which of two tactile distances fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
88
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 40 publications
(112 citation statements)
references
References 49 publications
(114 reference statements)
21
88
3
Order By: Relevance
“…Moreover, distortions in hand shape were strongly correlated in both conditions, r(24) = 0.725, p < 0.0001. However, as in Experiment 1, we did not find a modulatory effect of the type of instruction on these distorted representations (t (24) These results replicate previous reports showing similar anisotropy on the hand dorsum (Canzoneri et al, 2013;Green, 1982;Le Cornu Knight, Longo, & Bremner, 2014;Longo, Ghosh, & Yahya, 2015;Longo & Haggard, 2011;Longo & Sadibolova, 2013;Miller, Longo, & Saygin, 2014) Moreover, our results show that this is a robust effect that is not modulated by the attitude that participants assume in performing the task (i.e., apparent vs objective).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, distortions in hand shape were strongly correlated in both conditions, r(24) = 0.725, p < 0.0001. However, as in Experiment 1, we did not find a modulatory effect of the type of instruction on these distorted representations (t (24) These results replicate previous reports showing similar anisotropy on the hand dorsum (Canzoneri et al, 2013;Green, 1982;Le Cornu Knight, Longo, & Bremner, 2014;Longo, Ghosh, & Yahya, 2015;Longo & Haggard, 2011;Longo & Sadibolova, 2013;Miller, Longo, & Saygin, 2014) Moreover, our results show that this is a robust effect that is not modulated by the attitude that participants assume in performing the task (i.e., apparent vs objective).…”
Section: Resultssupporting
confidence: 90%
“…In previous research, strong correlations have been found between the magnitude of distortion on the two hands and across similar conditions for both tactile size perception (Longo et al, 2015a) and position sense (Longo and Haggard, 2010, 2012a; Longo, 2014; Mattioni and Longo, 2014). Thus, it is clear that reliable individual differences exist for both perceptual abilities.…”
Section: Introductionmentioning
confidence: 86%
“…Procedures for the tactile distance task were similar to our previous studies using this paradigm (Longo and Haggard, 2011; Longo and Sadibolova, 2013; Longo et al, 2015a). Stimuli were pairs of wooden posts mounted in foamboard, separated by 2, 3, or 4 cm.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations